Performance and emissions characteristics of biofuel blend in a CI engine - Ilkilic, Cumali (Sila Science, 2011)
Energy contents of vegetable oils are close to petroleum based oils, which make them renewable energy sources. It is under investigation to use various vegetable oils in diesel engines as alternative fuels. Owing to high viscosity and density, perfect atomization can't be attained and injection problems appear which lead to performance drops in the engine. In this study, biodiesel was obtained from cottonseed oil and its viscosity was lowered. Biodiesel with a viscosity close to diesel fuel was mixed with 25% by volume into the diesel fuel, called here as B25 fuel, and tested at a single-cylinder, air-cooled direct injection diesel engine to assess the performance at various speeds and engine powers. It was observed that torque output of the blend is 2% and power output is 1 % lower than diesel fuel, but specific fuel consumption is 1 % higher, and exhaust emissions lower than diesel fuel. The reduction in exhaust emissions have made the biodiesel a suitable alternative fuel for diesel engines and could contribute in controlling air pollution.
Keywords: biodiesel; alternative fuels; diesel engine; performance; exhaust emission